2012
DOI: 10.21608/jppp.2012.84099
|View full text |Cite
|
Sign up to set email alerts
|

LAND SNAILS ATTACKING PEA FIELDS: II- EFFICIENCY OF CERTAIN BIOCIDES AND MOLLUSCICIDES AGAINST Monacha SP. LAND SNAILS AT DAKAHLIA GOVERNORATE.

Abstract: This study was conducted at El-Mansoura district, Dakahlia Governorate during September-October 2011 on pea plantation to evaluate the efficiency of certain biocides compared with some Molluscicides against Monacha sp. Land snails on laboratory and field. Results can be concluded that Biogard, Cranch, Protecto and Vertimec were used with 1, 2 and 3 % concentrations as leaf dipping technique. LC50 and LC90 values were (2.84 and 18.75 %), (1.97 and 4.57 %), (4.99 and 25.29 %) and (0.63 and 2.56 %), respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…It helps in choosing the suitable integrated land snails management methods. The selection of control methods concept conditions depends on specific composition of the pests, the state and the density of their population Zedan et al, 2006 andMortada et al, 2012). The main aim of this work is to get more information about survey, population density and relationships between low or high snail population density and soil component in five districts at Kafr El-Sheikh governorate.…”
Section: Introductionmentioning
confidence: 99%
“…It helps in choosing the suitable integrated land snails management methods. The selection of control methods concept conditions depends on specific composition of the pests, the state and the density of their population Zedan et al, 2006 andMortada et al, 2012). The main aim of this work is to get more information about survey, population density and relationships between low or high snail population density and soil component in five districts at Kafr El-Sheikh governorate.…”
Section: Introductionmentioning
confidence: 99%
“…The present data of ABM toxicity on snail, H. aspersa are in accordance with some previous studies. There is an information of the toxic effects of ABM against land snails, where it had lethal toxic actions on the freshwater snails, Physa acuta [40], Biomphalaria alexandrina [41], land snails: Monacha contiana [42] and M. obstructa [43]. In addition, ABM was found to be more toxic on chocolate snail Eobania vermiculata [21,[44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Carbamate compounds had a wide range of effects and they are little affected by environmental conditions and their toxicity increase in humid surroundings, which are optimal for gastropods (Fouad et al,2004) (Shahawy, 2018) reported that Agrinate affected the activity of aspartate Aminotransferases (Ast), alanine Aminotransferases (Alt), total lipid (TL) and total proteins (TP). Finally, carbamate compound were more effective against land snails under laboratory and field conditions (EL-Okda et al, 1989;Fouly et al, 2002;Ismail et al, 2005., Mortada et al, 2012Geasa et al, 2013;Abd EL-Wahed 2014 andSamy et al, 2015). On the other hand, (Mortada et al, 2005) and (Ismail and Shetaia, 2009) reported that metaldehyde was more effective than methomyl in controling the land snail M cartusiana.…”
Section: Fig 1 the Activity Of Eobania Vermiculata Snails During Yementioning
confidence: 99%